Jamaica's decision to pursue a neoliberal development strategy : realignments in the state-business-class triangle. - HENKE, Holger (1999)
Examines the process of political coalition building surrounding Jamaican economic reform and the consequences for the country's foreign economic policy priorities. Aims to trace the political attitudes and situational conditions that facilitated the emergence and consolidation of a free market coalition between the state, various social classes, and particular sections of the business class.